Using Tegowangi Temple as A Source of Knowledge in Developing the Literacy of Members of the English Village of Pare - Arief, Muhammad Syaiful (Journal of Education Research, 2024)
This research aims to obtain the characteristics of the Tegowangi temple site as a source of knowledge in developing literacy for the English villagers of Pare; Utilization of the Tegowangi temple site as a source of knowledge in developing the literacy of English village members. This research uses a qualitative or naturalistic approach method that is oriented towards discovery, minimizing researcher manipulation of the research or study object. The informants for this research were one hundred members who studied the language in the English village of Pare, course tutors, several experts on temple architecture, and the caretaker of the Tegowangi temple site. The results of the research show  The characteristics of Tegowangi temple are referred to as Sentul temple, and Boedeng temple based on Dutch sources. Temple of Watsari, king of Matahun, brother-in-law of King Hayam Wuruk who died in one thousand three hundred and eighty eight.  Tegowangi temple site as an object for developing literacy through play, an object for summarizing learning, discussion as preparation for becoming a tourist guide, as an object for combining literacy and science, and literacy English language teaching. Members can care for and protect the local historical heritage of their ancestors which is still being preserved.